The causes of evolvability and their evolution - Payne, Joshua L.; Wagner, Andreas (Nature reviews. Genetics, 2019)
Evolvability is the ability of a biological system to produce phenotypic variation that is both heritable and adaptive. It has long been the subject of anecdotal observations and theoretical work. In recent years, however, the molecular causes of evolvability have been an increasing focus of experimental work. Here, we review recent experimental progress in areas as different as the evolution of drug resistance in cancer cells and the rewiring of transcriptional regulation circuits in vertebrates. This research reveals the importance of three major themes: multiple genetic and non-genetic mechanisms to generate phenotypic diversity, robustness in genetic systems, and adaptive landscape topography. We also discuss the mounting evidence that evolvability can evolve and the question of whether it evolves adaptively. In this article, Payne and Wagner discuss how recent experimental studies are complementing theoretical work to enhance our understanding of the evolvability of diverse biological systems. They highlight phenotypic heterogeneity, robustness and adaptive landscape topography as causes of evolvability, and they additionally discuss evidence for whether evolvability itself can evolve.